Climbing sports effect specific visual-spatial abilities - Pietsch, S.; Jansen, P. (Journal of Imagery Research in Sport and Physical Activity, 2018)
Physically active people show better visual-spatial abilities than physically inactive people. Especially athletes with response times based on competition times, such as wrestling, outperform other athletes. This quasi-experimental study examines the relationship of long-term activity in sport climbing, which is a typical non-response time-based leisure activity, and mental rotation and spatial visualization performance. Climbers outperformed other athletes in mental rotation, but not in spatial visualization tasks. That could be based on their experience with mainly holistic movement patterns.